Family Assistance Program With Interprofessional Education Approach In Labuan Panimba: Program Pendampingan Keluarga Dengan Pendekatan Interprofesional Edukasi Di Labuan Panimba - Putu Candriasih; Metrys Ndama; Hermin Austria Awusi (Poltekkes Kemenkes Palu, 2021)
Stunting is caused by multidimensional factors so that the handling needs to be done by multisectoral or interprofessional collaborations. Central Sulawesi is an area that still has many health problems regarding nutrition, in preventing various problems related to stunting, the role of the family and community plays a very important role in the recovery phase. The roles and functions of families and communities greatly affect the health conditions of individuals, families, groups, and communities. The results of the mentoring and assessment that became a problem were the provision of complementary feeding. The provision of appropriate complementary feeding according to recommendations and utilizing local wisdom can help prevent stunting, and can introduce healthy eating habits for mothers and children under two by utilizing nutritious food found in their environment. In addition, as an effort to make significant progress in improving the health and quality of children, especially in Indonesia. Conclusions in the handling of stunting, each team shall have the duty and authority so that there is no overlap. Teams of health workers who work for the handling of stunting are nutritionists, midwives, nurses and Promkes, village head. Each has their own duties and powers. The achievement targets for this community service are Modules and Intellectual Property Rights.